KERAGAAN F1 HASIL PERSILANGAN CABAI KERITING (Capsicum annuum L.) DI LAHAN GAMBUT - Yashi Indriani; Husna Yetti; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to obtain the F1 performance chili from crosses wrinkled chili that was grown in the peatland to be recommended as a genotype that has a high yield. This research lasted from January to June 2013 in Peatland experimental garden, Agriculture Faculty, University of Riau, Rimbo Panjang Village, Tambang district Kampar regency.This research used a randomized block design (RBD), consisting of 8 treatments (IPB C-111xC-120, IPB C-120xC-111,IPB C-111xC-159, IPB C-159xC-111, IPB C-120xC-159, Tanamo and Princess). The data were statistically analyzed by using analysis of variance, followed by Duncan’s test New Multiple Range Test (DNMRT) at the level of 5%. The result of this research showed that 8 chili genotypes had grown in the peatland had different potentials between a genotype with others and showed genotypes had adaptability quite good in peatland. All chili genotype showed nonsignificant weight per plant compare to Tanamo and Princess and result showed there was maternal effect for characters as a cross IPB C-120xC-159.   Keyword : Chili, Genotypes, Performance, peatland